2023
DOI: 10.3390/idr15040045
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus intermedius Brain Abscess with Lung Abscess and Aortic Valve Endocarditis: A Case Report and Literature Review

Francesca Gavaruzzi,
Pierangelo Chinello,
Giuseppe Cucinotta
et al.

Abstract: Streptococcus intermedius is frequently associated with brain and liver abscesses, while pleuropulmonary infections are considered rarer. Even less frequent is the association of lung and brain abscesses due to this agent with infective endocarditis. We describe the case of a 40-year-old man complaining of cough, fever, and headache who was diagnosed with a brain abscess due to S. intermedius, a concomitant lung abscess, and aortic native valve endocarditis. He was treated with surgical drainage of the brain a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…reported a patient with aortic valve endocarditis and severe aortic regurgitation that presented with unilateral pulmonary edema. In another article, Francesca Gavvaruzi et al 13 . reported a patient with aortic valve endocarditis and lung abscess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported a patient with aortic valve endocarditis and severe aortic regurgitation that presented with unilateral pulmonary edema. In another article, Francesca Gavvaruzi et al 13 . reported a patient with aortic valve endocarditis and lung abscess.…”
Section: Discussionmentioning
confidence: 99%
“…In a case report, Rana Al-Zakhari et al 12 reported a patient with aortic valve endocarditis and severe aortic regurgitation that presented with unilateral pulmonary edema. In another article, Francesca Gavvaruzi et al 13 reported a patient with aortic valve endocarditis and lung abscess. In our case, the patient had multiple lung lesions while having aortic valve endocarditis.…”
Section: Case Methodsmentioning
confidence: 99%
“…or mycobacteria [1]. Isolation of unusual pathogens, even in immunocompetent individuals, should carefully be considered as a cause of disease [20–22]. Hemoptysis may occur in LA, and may in rare cases be due to complicating pulmonary artery aneurysms [22].…”
Section: Clinical Presentationmentioning
confidence: 99%